INSTITUTIONAL MARKETING COMMUNICATIONS IN ROLE OF ATTRACTING FOREIGN DIRECT INVESTMENTS TO BOSNIA AND HERZEGOVINA - Mustafa Sinanagić; Beriz Čivić; Alma Kamarić (Economic Review)
The problem frequently faced by companies from transition and developing countries in attraction of Foreign Direct Investments (FDI) is lack of an adequate institutional framework which would adequately promote the potential those companies have through its activities, and with that also influence the attraction of foreign capital. The goal of this paper is to show the necessity of having such institutional framework, as well as institutional marketing communications which, together with other points of attraction of certain location in future, would be significant destination of inflows of FDI.